The Influence of the Work Budget Plan and Budget Realization Report on the Financial Performance of the North Sumatra Provincial Government - Nasirwan, Nasirwan; Sihombing, Andico Julius; Sibarani, Christy Amelia Rotua; Pasaribu, Benediktus Hasoloan (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This study was conducted with the aim of analyzing the influence of the budget work plan and budget realization report on the financial performance of the local government of North Sumatra Province. This study is expected to provide new insights into how budget planning can be improved to improve the financial performance of local governments. The research methodology in this journal uses descriptive quantitative methods, including historical data analysis and case studies, to evaluate the influence of the budget work plan on the financial performance of local governments. The objects used in this study are budget data from the website of the North Sumatra Provincial Government along with information regarding the financial reports of the North Sumatra provincial government, so this study was conducted using secondary data that has been provided directly by the North Sumatra Provincial Government. The data used is in the period of the 2021-2023 financial report. The results of this study are expected to provide recommendations for improvements in budget planning and financial management of the local government of North Sumatra Province.